Inclusión financiera y crecimiento económico en los países de Sudamérica periodo 2004 - 2020. - Reyes Espinoza, Miguel Angel (2023)
This research aims to investigate the relationship between financial inclusion and economic growth in South American countries, using data from nine South American countries (Argentina, Bolivia, Brazil, Chile, Colombia, Ecuador, Paraguay, Peru and Uruguay) during the period 2004-2020. The data include variables related to financial inclusion (such as savings and credit), economic growth (such as GDP) and other control variables (such as inflation and trade openness). The methodology applied is the pooled EGLS (cross-sectional random effects) method. The Swamy and Arora estimator is used to estimate the variances of the components, and the specification of the effects includes cross-sectional random effects and idiosyncratic random effects. The study finds a positive and statistically significant relationship between financial inclusion and economic growth in South American countries. Specifically, the coefficients of savings, credit and bankarization are positive and significant, indicating that an increase in financial inclusion leads to an increase in economic growth. The results are robust to various sensitivity tests, including the inclusion of additional control variables and the use of different estimation methods. In particular, efforts to increase access to credit and banking services can help to stimulate economic growth. The research is subject to several limitations, including time and potential omitted variable bias. In addition, it does not examine the mechanisms through which financial inclusion affects economic growth, such as increased investment or productivity. Overall, it provides evidence of a positive relationship between financial inclusion and economic growth in South American countries.